Legal Frameworks for Cybersecurity and Data Protection in Cloud-Based Notarial Systems in Indonesia: An Intersectional Analysis of Positive Law and Islamic Legal Principles - Sitaresmi, Adhisty; Rahmah, Mas; Wijoyo, Suparto; Anom, Adhitya Panji; Prayogo, Fatma Merve (al-'adalah, 2025)
This study aims to develop a hybrid legal framework that integrates Indonesia's positive Law with Islamic legal principles to regulate cloud-based notarial practices. This research is motivated by the increasing use of digital technology, particularly cloud computing, in notarial services. On one hand, this development offers greater convenience and efficiency, but on the other hand, it also raises serious concerns regarding cybersecurity and the protection of personal data. Employing a normative juridical method supported by conceptual and comparative approaches, this qualitative literature study examines key legal instruments, including the Electronic Information and Transactions Law (ITE Law), the Personal Data Protection Law, and the Notary Law, alongside classical and modern sources of Islamic jurisprudence. The analysis reveals a normative gap in Indonesia’s existing regulations concerning notaries' responsibilities in digital settings. In addressing this issue, Islamic principles such as amanah (moral responsibility), maslahah (public interest), and ḥifẓ al-māl (protection of wealth) provide ethical foundations that can meaningfully support and strengthen the legal framework. The main finding highlights that the integration of these legal systems not only strengthens the legal protection of data but also enhances public trust by embedding ethical values within regulatory structures. This research contributes a practical and conceptual model for digital notarial governance that is technologically responsive and culturally rooted, supporting the formulation of future regulations in Indonesia